2022
DOI: 10.18632/aging.204125
|View full text |Cite
|
Sign up to set email alerts
|

The circular RNA hsa_circ_0003091 regulates sepsis-induced lung injury by sponging the miR-149/Smad2 axis

Abstract: Sepsis-induced acute lung injury (ALI) is a severe cause of death. Increasing evidence has identified circular RNAs (circRNAs) acting as critical regulators of human diseases. However, their expression pattern and underlying mechanisms in ALI remain unclear. Herein, we screened the circRNAs of ALI patients and constructed a lung injury murine model using lipopolysaccharides (LPS) induction. Functional analyses of targeted circRNA were performed in vivo and in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…These studies provided references for our study, and we constructed sepsis-induced ALI models by treating mice or A549 cells with LPS to explore the functional role of circTDRD9. CircTDRD9 was previously recorded to be upregulated in mice with the tracheal administration of LPS (15). Consistent with the previous data, our study presented that the expression of circTDRD9 was increased in LPS-treated A549 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies provided references for our study, and we constructed sepsis-induced ALI models by treating mice or A549 cells with LPS to explore the functional role of circTDRD9. CircTDRD9 was previously recorded to be upregulated in mice with the tracheal administration of LPS (15). Consistent with the previous data, our study presented that the expression of circTDRD9 was increased in LPS-treated A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…RNA sequencing provided numerous circRNAs that were differently expressed in LPS-induced sepsis in animal models (13,14). Among these circRNAs, we found that circ_0033530 was shown to be significantly upregulated in sepsis patients (15). Circ_0033530 is produced from tudor domain containing 9 (TDRD9), also named circTDRD9 in this study.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, circBIRC6 contains miR-145 and miR-34a binding sites to regulate human cell pluripotency ( Yu et al, 2017 ). Some other circRNAs also can sponge microRNAs, despite the majority of them only have a limited amount of microRNA binding sites ( Panda 2018 ; Qiu et al, 2021 ; Shen et al, 2022 ). Further researches are required to identify in what extend circRNAs could sponge microRNAs due to the lower expression of circRNAs.…”
Section: Acting As Microrna Spongesmentioning
confidence: 99%
“…For instance, circHIPK3 serves as a sponge for miR-29b to enhance the repair of intestinal epithelial cells in patients with sepsis [16]. Furthermore, circTLK1 promotes inflammation and oxidative stress via the miR-106a-5p/HMGB1 axis in sepsis-associated acute kidney injury, and hsa_circ_0003091 mediates sepsisinduced lung injury by reducing miR-149 [17,18]. Although several studies have revealed that circRNAs are involved in intestinal epithelial injury in sepsis [16,19,20], few studies have investigated the roles of circRNAs in intestinal epithelial apoptosis.…”
Section: Introductionmentioning
confidence: 99%